2019
DOI: 10.1093/jcbiol/ruz087
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a microbiome in the midgut trunk of six representative Crustacea

Abstract: It has become a common expectation for an animal’s guts to be a site for bacterial symbiosis, which may play a role in influencing various aspects of physiology including digestion and immune responses. The presence of a microbiome in the digestive tracts of crustaceans has been demonstrated in the past using molecular techniques and has encouraged manipulations including probiotics to enhance growth rates in cultured species. We suggest, however, that bacteria are restricted to the lumen of the gut and separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
0
17
4
Order By: Relevance
“…According to our observations, Deferribacteres cells are in direct contact with their host. This contradicts previous reports on shrimps and crustaceans more generally (Martin et al, 2020; Vogt, 2021). In Artemia salina , Daphnia magna , Gammarus sp., Homarus americanus , Tigriopus californicus and Sicyonia ingentis , microorganisms appear in the midgut tube and hindgut of crustaceans, located in the alimentary bolus within the endoperitrophic space (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…According to our observations, Deferribacteres cells are in direct contact with their host. This contradicts previous reports on shrimps and crustaceans more generally (Martin et al, 2020; Vogt, 2021). In Artemia salina , Daphnia magna , Gammarus sp., Homarus americanus , Tigriopus californicus and Sicyonia ingentis , microorganisms appear in the midgut tube and hindgut of crustaceans, located in the alimentary bolus within the endoperitrophic space (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Most arthropods construct a physical barrier composed of chitin in their midgut called a peritrophic matrix (PM) 4 , 5 . This suggests that the intestinal microbiota that colonize the gut epithelia is a derived feature of mammal, which lacked in other organisms 6 , including crustacean 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbiome present on the feed given to lobsters was not assessed. This is important because Martin et al (2020) showed that the lumen of the midgut of American lobsters, as well as 5 other crustaceans from disparate taxa, have no microbiome per se. The microbiome is solely present within the food bolus which is entirely encased by the peri trophic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no work on the gut microbiome of the American lobster, a recent study has examined how the formation of gut microbiome changes in the European lobster H. gammarus (Holt et al 2020). In addition, using ultrastructure and specialized staining, Martin et al (2020) found that American lobsters and several other crustaceans do not have an active microbiome in the midgut region because the food bolus is encased in a peritrophic membrane that excludes bacteria from entering the lumen of the midgut.…”
Section: Introductionmentioning
confidence: 99%